Modelling and measurement of transient torque converter characteristics - Li, Yang; Sundén, Max (My University, 2016)
The torque converter is a crucial component in the drivetrain of a vehicle equipped with an automatic gearbox. It has the ability to transfer power with torque amplification, allow slip between engine and transmission and dampen vibrations between the two. For these reasons its characteristics will have a direct effect on the vehicle’s performance, fuel economy, drivability and comfort. The behaviour of the torque converter is often modelled based on standardised component testing in the form of measured steady-state performance. It is however known that transient dynamics can have a significant impact under certain conditions, such as vehicle take-off. In order to aid the development of high quality products it is desired to predict component behaviour with as high accuracy as possible. For a vehicle manufacturer such as Volvo Cars, it is usually of higher importance to accurately capture real-world driving conditions and to specify performance targets that can be linked to customer sensation rather than mechanical properties. In this thesis, transient simulation models based on steady-state measurements, used at Volvo Cars were evaluated against measurement data to investigate if they could be parameterised to simulate the behaviour of other torque converters, even under transient conditions. A model based on hardware parameters rather than measured behaviour was also implemented and evaluated.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering